(untitled) (Economic studies journal, 2019)
This research empirically examines the impact of two dimensions of Hofested’s (2010) cultural dimensions on emotional intelligence (EI) of nurses at Misurata Medical Center (MMC). The research aims to explore theories and highlight interpretations of research participants regarding research topic, and to test the relationship between Masculinity and Indulgence, in one hand, and EI on the other hand. It also aims to determined differences among participants in relation to their demographic data in effecting levels of EI. Therefore, a mixed research design were adopted to achieve its aims. This has led to apply two research stages; firstly, is trough conducting 10 semi-structured, as data was analysed according to Qualitative Data Analysis Techniques (QDA). Secondly, a questionnaire was administered to measure the research variables. Therefore, 175 questionnaires, out of a population of 326, were distributed. However, data was statistically analysed the significant results were highlighted. The most highlighted results are; nurses at MMC have shown high levels of EI of about 81%, results have highlighted that sex and years of service have no significant correlations with EI. On the other hand, they have reaffirmed that ages are correlated with EI by 0.043. However, results have confirmed that both masculinity and restraint have shown significant associations with EI of 0.212 and 0.031 subsequently. Based on these results, the researchers have discussed that nurses who show high levels of EI should be giving more advantages and such behaviours should be encouraged at MMC. Furthermore, all ages of nurses should be encouraged engage in EI behaviours.